How the idea of religious toleration came to the West - Zagorin, Perez (Princeton University Press, 2004)
Publisher's description: Religious intolerance, so terrible and deadly in its recent manifestations, is nothing new. In fact, until after the eighteenth century, Christianity was perhaps the most intolerant of all the great world religions. How Christian Europe and the West went from this extreme to their present universal belief in religious toleration is the momentous story fully told for the first time in this timely and important book by a leading historian of early modern Europe. Perez Zagorin takes readers to a time when both the Catholic Church and the main new Protestant denominations embraced a policy of endorsing religious persecution, coercing unity, and, with the state's help, mercilessly crushing dissent and heresy. This position had its roots in certain intellectual and religious traditions, which Zagorin traces before showing how out of the same traditions came the beginnings of pluralism in the West. Here we see how sixteenth- and seventeenth-century thinkers--writing from religious, theological, and philosophical perspectives--contributed far more than did political expediency or the growth of religious skepticism to advance the cause of toleration. Reading these thinkers--from Erasmus and Sir Thomas More to John Milton and John Locke, among others--Zagorin brings to light a common, if unexpected, thread: concern for the spiritual welfare of religion itself weighed more in the defense of toleration than did any secular or pragmatic arguments. His book--which ranges from England through the Netherlands, the post-1685 Huguenot Diaspora, and the American Colonies--also exposes a close connection between toleration and religious freedom. A far-reaching and incisive discussion of the major writers, thinkers, and controversies responsible for the emergence of religious tolerance in Western society--from the Enlightenment through the United Nations' Universal Declaration of Human Rights--this original and richly nuanced work constitutes an essential chapter in the intellectual history of the modern world.